Outcome Predictors of Stroke Mortality in the Neurocritical Care Unit - Viderman, Dmitriy; Issanov, Alpamys; Temirov, Talgat; Goligher, Ewan; la Fleur, Philip (Frontiers in Neurology, 2020)
Abstract Background: Risk factors for medium to long-term mortality after stroke are well established but predictors of in-hospital stroke mortality are less clearly characterized. Kazakhstan has the highest age-standardized mortality rate from ischemic stroke in the world. Methods We performed a retrospective analysis of patients with stroke who were admitted over a 3.5-year period to the neurocritical care unit of a tertiary care hospital in Nur-Sultan, Kazakhstan. Results In total, 148 critically ill patients were included in the analysis (84 ischemic stroke, 64 hemorrhagic stroke). The mean age was 63 years, 45% were male and the mean Glasgow Coma Score (±SD) at baseline was 10.3 (±3.4). The in-hospital mortality rate was similar in patients with ischemic (36%) and hemorrhagic (39%) stroke (HR 0.88, 95%CI 0.48-1.60). Median survival was 38 days (range: 1-89 days) in patients with ischemic stroke and 39 days (range: 1-63 days) in patients with hemorrhagic stroke. Univariable analysis found that patients who had a lower Glasgow Coma Scale, were in coma and who had cerebral edema were more likely to die in-hospital (P = 0.04, 0.02, <0.01, respectively). Conclusions Our analysis showed that mortality risk in critically ill patients with hemorrhagic stroke was closer to mortality risk in patients with ischemic stroke than has been reported in other analyses. Hypertension, chronic heart failure, ischemic heart disease and atrial fibrillation were the most frequent comorbidities in patients who developed severe (life-threatening) stroke. Coma and cerebral edema on admission appear to be associated with poor outcome. This is the first publication of in-hospital stroke mortality from a Central Asian population and could form the basis for future research including development of risk scores and identifying modifiable risk factors.